2014
DOI: 10.1016/j.seizure.2014.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy, comorbid conditions in Canadian children: Analysis of cross-sectional data from Cycle 3 of the National Longitudinal Study of Children and Youth

Abstract: These results provide an initial prevalence estimate of comorbid conditions with epilepsy in Canadian children. In a high proportion of children with epilepsy, the PMK had reported at least one comorbid disorder. These findings carry implications for health care utilization and long-term outcomes. We discuss methodological aspects related to the ascertainment of epilepsy in both surveys, and to the validity and implications of our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Through our review, we also identified a few instances of missed opportunities to report on the overall occurrence of intellectual disabilities. For example, two studies using large and nationally representative samples of children and youth analyzed data about the presence of intellectual disabilities; however, they did not provide an overall prevalence estimate [64,65]. When subgroups are compared, results could easily be presented in such a way as to allow the calculation of an overall prevalence thereby making an additional contribution to the body of literature.…”
Section: Discussionmentioning
confidence: 99%
“…Through our review, we also identified a few instances of missed opportunities to report on the overall occurrence of intellectual disabilities. For example, two studies using large and nationally representative samples of children and youth analyzed data about the presence of intellectual disabilities; however, they did not provide an overall prevalence estimate [64,65]. When subgroups are compared, results could easily be presented in such a way as to allow the calculation of an overall prevalence thereby making an additional contribution to the body of literature.…”
Section: Discussionmentioning
confidence: 99%
“…1 Unmanaged, epilepsy can result in cognitive decline, social isolation, and poor quality of life and has substantial economic impact on families and society. 2 Up to 30% of children with epilepsy continue to have seizures while on anti-seizure medication, a condition known as drug-resistant epilepsy (DRE). Novel neurotechnologies, including minimally invasive and neuromodulatory options for seizure control, represent a new frontier for improving the subjective and objective quality of life for pediatric DRE patients, 3 but best practices for treatment do not currently exist.…”
mentioning
confidence: 99%
“…For further information on weighting or other methodological issues relating to the NLSCY, the reader is advised to refer to Statistics Canada user guides 2 and to previous papers using NLSCY data. [4][5][6][7] Disparities in the reported rates of the NDD by gender were estimated by logistic regression for cycle 3, as this cycle had the largest number of respondents in the survey reporting any of the four conditions of interest. Missing data in the remaining cycles only constituted approximately 4.28% of the total number of participants in the survey and was treated as missing at random and excluded from the analysis.…”
Section: About the Nlscy And Sample Designmentioning
confidence: 99%
“…The primary objective of the NLSCY was to monitor the development and well-being of Canada's children during their progress from infancy to adulthood. The dataset that includes four cycles of cross-sectional data and eight cycles (5)(6)(7)(8) of longitudinal data provide a population-based sample of children and youth in Canada. The dataset (cycles 1-4) has been used to estimate the prevalence of chronic health conditions and determination of child and youth health outcomes [2][3][4][5] The authors used survey data in a prior study to determine the prevalence of childhood epilepsy in cycle 3 and outcomes-related comorbid conditions in previous publications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation